2013
DOI: 10.1111/add.12126
|View full text |Cite
|
Sign up to set email alerts
|

Population drinking and drink driving in Norway and Sweden: an analysis of historical data 1957–89

Abstract: In Norway and Sweden, as total population level of alcohol consumption increases or decreases so does the incidence of driving while intoxicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It has been hypothesised that alcohol consumption at a population level (ie, per-capita alcohol consumption) is associated with driving under the influence of alcohol 15 . If correct, an unintended outcome of a change in BAC legislation could be a reduction in per-capita alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesised that alcohol consumption at a population level (ie, per-capita alcohol consumption) is associated with driving under the influence of alcohol 15 . If correct, an unintended outcome of a change in BAC legislation could be a reduction in per-capita alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…I T IS WELL recognized that alcohol intoxication contributes to a large proportion of traffic and nontraffic injuries in many countries (Skog, 2001a). Previous studies show that about 10 to 60% of all fatal traffic crashes appear to be alcohol-related and the countries with low alcohol consumption levels were found to have low alcohol-related traffic crash rates (Norstr€ om and Rossow, 2013). Furthermore, alcohol also plays a significant role in nontraffic injuries, such as accidental falls and drowning, injuries caused by fire, and other unintentional injuries .…”
mentioning
confidence: 99%
“…The study's area-based analyses, using Norwegian and Swedish data, demonstrated a strong and statistically significant association; as alcohol consumption per capita increases or decreases, so does the incidence of driving under the influence of alcohol. 22 We are not aware of any studies that have evaluated whether or not a legal reduction in the BAC limit (for a whole country) has led to a reduction in that country's population drinking. This could be a wider, unintended, outcome that can be attributed to change in BAC legislation.…”
Section: Association Between Blood Alcohol Concentration and Populatimentioning
confidence: 99%